PENGARUH POLA ASUH ORANG TUA TERHADAP KECERDASAN INTERPERSONAL REMAJA - Ayu Widyaningrum; Farhana Farhana (STIT AL-AMIN KREO TANGERANG, 2023)
The focus of this study is to examine parenting styles that are limited to one type of parenting, namely permissive parenting. This study aims to determine the influence of permissive parenting on interpersonal intelligence in adolescents. This study used a quantitative approach with a descriptive method of correlational analysis. Using a questionnaire instrument distributed to 31 samples from 100 total adolescent populations in Rw. 007 Jl. Petojo Enclek, Central Jakarta. The questionnaire instrument amounted to 20 positive and negative statements on each variable X and Y. This study showed the results that there was an influence but very weak or low on permissive parenting on adolescent interpersonal intelligence, this proof came from the ro rt hypothesis test with ro results of 0.113 then the results were smaller than the